'Exchanging Cuba for 1 Million YouTube Views': Technological Precarity, Offline Virality, and 'Patria y vida'. Issue 3 (October 2022) - LEVINE, MIKE
Abstract: For many Cubans, the internet remains an inaccessible destination. The residents of repartimiento districts – Black Cuban residents from outlying districts across Havana – manage the situation through custom solutions that bridge gaps of technological precarity. Utilizing USB drives to share content with one another, artists and music fans have constructed a complex, alternative internet that allows for the peer-to-peer trade of movies, music, and other media. Pirate digital networks such as el paquete semanal and Zapya, for instance, circulate music across the island without the need to rely on costly and unreliable internet infrastructure. Utilizing interviews, physical and digital ethnographies, and theories of viral musicking, I argue that Black Cuban artists and music fans, despite internet scarcity, use alternative networks to generate viral events. In particular, Cubans in 2021 joined in a transnational expression of sonic protest through the popularity of the politically subversive song 'Patria y vida', a song that circulated widely through underground, USB-based networks. In this article, I discuss the song's construction, circulation, and role in sounding the J-11 Cuban protests to demonstrate how Black Cuban artists and fans share music through USB-based networks not only to solve gaps in technologically precarious situations, but also to generate powerful moments of viral musicking.